MERWIYAT IBN WARA (D. 270 AH) In The GREAT SUNAN Of IMAM Al-NASI (303 AH) COLLECTION And STUDY - ABOUD , ABDEL WAHAB (Islamic Sciences Journal, 2023)
Praise be to Allah, the Lord of the Worlds, and prayers and peace be upon our master Muhammad, the messenger, a mercy to the worlds and his family and companions, who have preserved the Book of their Lord, and who have spoken the Sunnah of their Prophet and have communicated it to the pure and pure people .After: The Noble Sunnah is the second source of legislation in Islam after the book of Allah, it is an explanation and explanation for it, and this is why the Prophet peace be upon him, the world even between the people what came down to them from their Lord and left them on the clear argument for the night of Knharha. God has created from this nation, men of science and virtue saved the Sunnah of the Prophets, and wrote it, and showed them to the people, and defended them, and Mahsouha, and drove out of what was an outsider, and so in every generation until it reached us pure free of impurities and falsehood, and will remain with permission God is safe and reserved for the hour, as the Prophet (peace and blessings of Allaah be upon him) told him: "A group of my faithful people are still not harmed by those who have failed them until the Hour is over. They are the owners of the hadeeth. Their benefits, we recognize them thanks to them, and share with people their beautiful exploits and great deeds, and What prompted me to write in the science of the Hadith, wishing God Almighty to serve the Sunnah purified, and reviving the biography of the flag of the honorable Sunnah, Imam Ibn Wara, may God have mercy on him, who spent his age in the service of this religion, has been limited to study Merawiat in the Great Sunan For the Imam of women, to clarify the science of the Sunnah of the Prophet, and to highlight its importance through the personalities who transferred to us the conversations of the Prophet peace be upon him, and the collection of these conversations among the books that included these ahaadeeth, and the statement of the personality narrator of these ahaadeeth, , To stand on the validity of these ahaadeeth And so on and so on, to benefit him and others in the application of the Sunnah of the Prophet's purification, so I opted for (Marwaat Imam Ibn Wara in the great Sunan Al-Imam women gathering and study), and dealt with research and study, this research after this introduction to three investigations and conclusion, In conclusion, we would like to mention the most important results that we have reached through this study, namely that Imam Ibn Wara (may Allaah have mercy on him) is Imam Muhammad ibn Muslim Ibn Othman bin Abdullah Al-Razi, who was educated by many imams of the media, Al-Mubarak, and Al-Haytham ibn Jameel), as well as on his hands Or many, as (Ibn Abi Asim and Women), has praised him is one of the scholars, pampered so his confidence and sincerity and health Achtharh between the imams and scholars and maintain, and that the Imam Women's Almighty God's mercy is the Imam Ahmad bin Shoaib bin Ali female judge. And was taught by many of the imams media such as (Qutaybah Ibn Said, Ibn Wara), as taught by the flags of many, such as (Abu Qasim Kanani, Muhammad ibn Qasim Andalusian), and praised by one of the scientists, and thus to his confidence and honesty And the validity of his fame among the imams and scholars and conservation, and that the study included Marwaites Imam Ibn Wara may Allah have mercy on him through the great Sunan of Imam women (3) newly, and the result was after the study of the verses of the hadiths as follows: (1) 1) a good bond, and (1) a weak bond. Finally, I ask Allaah to make us who are the Prophet (peace and blessings of Allaah be upon him) and the Sahaabah and the followers, may Allah be pleased with them all, their good voices, And our last prayer is that the Praise be to Allah, the Lord of the Worlds, and God prayed to our master Muhammad and his family and companions and gave him a great recognition to the Day of Judgment.